Piperazine functionalized magnetic sporopollenin for solid phase extraction of lead(II) / Naqhiyah Farhan Ahmad - Naqhiyah Farhan , Ahmad (2018)
The present work describes the successful functionalization/magnetization of bio-polymeric spores of Lycopodium Clavatum (sporopollenin) with 1-(2-hydroxyethyl) piperazine. Characterization techniques i.e., Fourier Transform Infra-red (FT-IR), Field Emission Scanning Electron Microscope (FESEM), Energy-Dispersive X-ray Spectroscopy (EDS), Powder X-Ray Diffraction (PXRD) and Vibrating Sample Magnetometer (VSM) were used to confirm the formation of 1-(2-hydroxyethyl) piperazine functionalized magnetic sporopollenin (MNPs-Sp-HEP). The proposed material was used as an adsorbent for the adsorption of noxious Pb(II) ions metal ion from aqueous media through a batch-wise method. Adsorption isotherm studies revealed that Langmuir model well-fitted to experimental data as compared to Freundlich isotherm. Maximum adsorption capacity (qm) of Pb(II) ions is 13.29 mg g-1. Thermodynamic parameters such as free energy (ΔG°), entropy (ΔS°) and enthalpy (ΔH°) were also investigated from the adsorption studies and were used to elaborate the mechanism of their confiscation. The successful synthesized modified sporopollenin was future optimized for magnetic solid-phase extraction (MSPE) of Pb(II) ions from environmental samples. The pre-concentration and determination of Pb(II) ions were conducted by Flame Atomic Absorption Spectroscopy (FAAS). The best working conditions were as follow; pH 6.5, 15 min of extraction time, 0.3 mol L-1 HNO3 as elution solvent, 10 min of desorption time and 25 mg of adsorbent dosage. Under the optimized condition, the analytical performances were determined with pre-concentration factor (PF) and limits of detection (LOD) are 47 and 0.005 mg L-1, respectively. The reusability studies suggested that the newly synthesized adsorbent could be used up to five cycles. The proposed method was performed to analyze Pb(II) ions in real water samples from river water, tap water and leachates.